High Precision Tri-Axial Quartz Flexible Accelerometers Resolution Measurement Method Based on Tri-Axial Turntable - Chunxi Zhang; Minpeng Dai; Wei Luo; Xiong Pan (IEEE Access)
Aiming at the high requirements of the experimental equipment for the measurement of high precision quartz flexible accelerometer resolution, the gravity measured by high precision tri-axial accelerometers was subdivided by the tri-axial turntable. Tri-axial quartz flexible accelerometers resolution measurement model was established and general mathematical expression for the resolution measurement was derived. Based on the mathematical expression, the effective angle range that satisfied the measurement condition was given out. Besides, the tri-axial quartz flexible accelerometers resolution measurement process was designed. Within the effective angle range, numerical simulations were performed and the simulation results showed that: the proposed method can theoretically measure tri-axial quartz flexible accelerometers of which the resolution was about 10−6g. Then the tri-axial quartz flexible accelerometers resolution repetitive measurement experiments were carried out and the experimental results illustrated that: the difference between the measured value with the theoretical value is within $1~μ \text{g}$ , which met the requirements for use. In addition, the resolution of tri-axial quartz flexible accelerometers can be measured at one time based on the designed process, demonstrating that the proposed method was valid.